2018
DOI: 10.1101/421370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct nanoscale calcium channel and synaptic vesicle topographies contribute to the diversity of synaptic function

Abstract: SUMMARYThe nanoscale topographical arrangement of voltage-gated calcium channels (VGCC) and synaptic vesicles (SVs) determines synaptic strength and plasticity, but whether distinct spatial distributions underpin diversity of synaptic function is unknown. We performed single bouton Ca2+ imaging, Ca2+ chelator competition, immunogold electron microscopic (EM) localization of VGCCs and the active zone (AZ) protein Munc13-1, at two cerebellar synapses. Unexpectedly, we found that weak synapses exhibited 3-fold mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 91 publications
(158 reference statements)
0
24
0
Order By: Relevance
“…Nakamura et al, 2015), while Ca 2+ signals remained unaltered at parallel-fiber boutons (Baur et al, 2015). We found that neither amplitudes nor time courses or durations of influx of single-bouton Ca 2+ transients were different between age groups (Figure 3), indicating that neither Ca 2+ influx nor buffering were different between age groups (Sabatini and Regehr, 1998;Schmidt et al, 2003;Bornschein et al, 2013;Rebola et al, 2018). In addition, the CV of Ca 2+ amplitudes upon repeated activation of individual boutons was not different between age groups (Figure 3), indicating that similar numbers of VGCCs opened during an AP at young and mature terminals (Sabatini and Svoboda, 2000).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Nakamura et al, 2015), while Ca 2+ signals remained unaltered at parallel-fiber boutons (Baur et al, 2015). We found that neither amplitudes nor time courses or durations of influx of single-bouton Ca 2+ transients were different between age groups (Figure 3), indicating that neither Ca 2+ influx nor buffering were different between age groups (Sabatini and Regehr, 1998;Schmidt et al, 2003;Bornschein et al, 2013;Rebola et al, 2018). In addition, the CV of Ca 2+ amplitudes upon repeated activation of individual boutons was not different between age groups (Figure 3), indicating that similar numbers of VGCCs opened during an AP at young and mature terminals (Sabatini and Svoboda, 2000).…”
Section: Discussionmentioning
confidence: 75%
“…It is still conceivable that AP duration shortens developmentally as in the calyx of Held (Taschenberger and von Gersdorff, 2000;Nakamura et al, 2015), if it were counterbalanced by changes in VGCC gating. Since electrophysiological recordings from small cortical boutons in slices still pose a challenge, we analyzed the rise times of Ca 2+ signals and the temporal derivatives of the signals as a proxy for the duration of the presynaptic Ca 2+ current (Sabatini and Regehr, 1998;Rebola et al, 2018). The 10%-90% rise times (young: 0.75 ms, 0.69-0.86 ms, n = 7; mature: 0.90 ms, 0.80-0.76 ms, n = 5; p = 0.639, MWU) and the SDs of Gaussian functions fit to the derivatives of the Ca 2+ signals (young: 217 ms, 191-234 ms; mature: 235 ms, 189-242 ms; p = 0.343, MWU) were not different among age windows ( Figure 3G), supporting the notion of similarity in Ca 2+ influx.…”
Section: Presynaptic Ca 2+ Transients Are Not Different Between Age Gmentioning
confidence: 99%
See 1 more Smart Citation
“…At zebrafish NMJ and mouse mossy fiber synapses, the P/Q type has been shown to have a higher open probability than N type, which would be expected to result in greater calcium influx upon action potential (Li et al, 2007;Naranjo et al, 2015). In addition, calcium accumulation also depends on both the density and location of calcium channels (Dittrich et al, 2018;Rebola et al, 2019). Should the P/Q channels occur at higher density the domains formed by calcium influx would experience greater overlap, thereby increasing local calcium concentration (Stanley, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Should the P/Q channels occur at higher density the domains formed by calcium influx would experience greater overlap, thereby increasing local calcium concentration (Stanley, 2016). Furthermore, there might be channel type specific differences in coupling between presynaptic calcium influx and the calcium sensor for release, a critical determinant for synaptic efficacy (Eggermann et al, 2011;Rebola et al, 2019). Tighter coupling has been shown for the several central synapses that rely on P/Q type, while looser coupling is often associated with weaker synapses that use the N-type for release (Iwasaki and Takahashi, 1998;Wu et al, 1999;Forti et al, 2000;Stephens et al, 2001;Hefft and Jonas, 2005;Bucurenciu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%